ICAR-DMAPR’s classical journey in medicinal and aromatic plant research and advancement - Das, Manish; Pandey, Sudhakar (Indian Horticulture, 2023)
Medicinal and aromatic plants (MAP) have occupied an important position in the socio-cultural, spiritual and medicinal arena of rural and tribal lives of India. They have contributed immensely by producing diverse range of plant based intermediary compounds and value-added downstream end products used in several applications; drug formulation, food flavouring, perfumery, culinary, toiletry, heath products, food supplements, cosmetics, incense and other anthropogenic applications and animal care products. MAP are in use since time immemorial with the recognition that smelling, chewing, and/or eating of some plant materials could provide relief from nausea, pain, and/or other infirmities. With the advancement of knowledge led by scientific innovations, the MAP are gradually gaining importance.